Le roman-feuilleton ou l'écriture mercenaire : l'exemple des Mystères de Paris - Anaïs Goudmand (Cahiers de Narratologie)
This paper aims at analysing the narrative consequences of daily publication by studying the means of narrative tension in the serial organization, with particular emphasis on the example of Les Mystères de Paris by Eugène Sue, which were published between 1842 and 1843 in Le Journal des débats.